2011
DOI: 10.3109/17435390.2010.551428
|View full text |Cite
|
Sign up to set email alerts
|

Human skin penetration of gold nanoparticles through intact and damaged skin

Abstract: Gold nanoparticles (AuNPs) are produced for many applications but there is a lack of available data on their skin absorption. Experiments were performed using the Franz diffusion cell method with intact and damaged human skin. A physiological solution was used as receiving phase and 0.5 mL (1st exp) and 1.5 mL (2nd exp) of a solution containing 100 mgL and 7.1 ± 2.5 ng cm-2 h -1 in intact and damaged skin, respectively, with a lag time less than 1 hour. Transmission Electron Microscope analysis on skin samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…A recent report by Larese Filon et al (2011) supports the earlier findings of Sonavane. They found similar results when evaluating gold nanoparticle penetration (12.9 nm) in thawed human skin (29). Gold nanoparticles were detected in the receiving solution of the Franz cells after 24 h of skin exposure.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…A recent report by Larese Filon et al (2011) supports the earlier findings of Sonavane. They found similar results when evaluating gold nanoparticle penetration (12.9 nm) in thawed human skin (29). Gold nanoparticles were detected in the receiving solution of the Franz cells after 24 h of skin exposure.…”
Section: Introductionsupporting
confidence: 53%
“…These data were gathered from a depth series of en face images. 24 h using ICP to detect gold ions in the receptor (29). Our study showed penetration into stratum corneum but not beyond using 14.9-nm gold nanoparticles in aqueous solution with TEM, MPT-FLIM, and RCM.…”
Section: Discussionmentioning
confidence: 70%
“…The same author also reported the effect of surface modifications, size, vehicles, and concentrations of AuNPs over human skin permeation19. Larese et al 20. performed permeation experiments on intact and damaged human skin and reported that the AuNPs penetrated deeper in the layer and flux of AuNPs for damaged skin was an order of higher than that of intact skin.…”
mentioning
confidence: 98%
“…Excised human skin is often stored for a period of 24 hours to several weeks under varying temperatures ranging from 4°C to −80°C before it is used for NP penetration studies by different groups. It is important to note that skin handling, storage and processing parameters may alter the results obtained [11,16,59,60]. Pentland et al, demonstrated that skin trauma induced during subcutaneous fat removal causes mast cell degranulation and increases tissue vascularity [42].…”
Section: Resultsmentioning
confidence: 99%